COMPARISON OF GROWTH RATE OF THREE CATFISH (Pangasius Hypopthalmus) WITH DIFFERENT KINDS OF FEED - RAHMADINA RAHMADINA; NOVIA ANGGREYNI BATU BARA (KLOROFIL: Jurnal Ilmu Biologi dan Terapan, 2019)
Feed is one factor that can support the development of fish farming is intensive and semi-intensive, both freshwater fish, brackish water fish, and sea water fish. While the feed required by the fish since the start of the size of the larvae (fry), up to the size of the parent. However, the feeding of the fish also can be creation to maximize growth. Fish growth is strongly influenced by the quality of the feed and therefore the need to do research, causes of a different kind of feed to seed the growth hormone of catfish. Here the research I did was observe the ratio of the growth rate of catfish that I give a different feed types among which the pellets, the remains of fish and leaves. The research of method used in this study is a quantitative method that is located in the home. And the observation time that I did was for 9 weeks. It turned out that the results shown by the fastest growth in the given fish feed pellets.